FEATURES OF PROACTIVE PERSONALITY AND AUTO-AGGRESSIVE BEHAVIOR OF PERSONS DEPRIVED OF LIBERTY - Kwiatkowski, Bartosz (Studia Psychologica: Theoria et praxis, 2022)
The obligation to be imprisoned in penitentiary isolation causes personal damages in the form of emotional, motivation or behavioral disorders. The negative effect of depriving needs of prisoners is their increased tendency to perform intentional self-harm while serving imprisonment. In addition to factors favoring the occurrence of self-aggressive behaviors of prisoners, there is also a specific number of protective factors that are admittedly less frequently the subject of research studies. The article discusses the results of our own research, which proved that proactivity as a personality trait has a negative relationship with self-aggression. In addition, it has been shown that proactive convicts have significantly longer intervals between acts of self-aggression, as well as their proactive activities coexist with declarations of the desire to stop self-harm in the future.